2019
DOI: 10.1108/jsbed-12-2017-0387
|View full text |Cite
|
Sign up to set email alerts
|

SMEs capital structure: trade-off or pecking order theory: a systematic review

Abstract: Purpose The purpose of this paper is to organize and present the literature related to firm’s capital structure across the years and find the most relevant publications and authors in the research area. Moreover, the authors pretend to fill the gap in the literature by studying different works and their compatibility with the main theories. Design/methodology/approach The systematic literature review is conducted by using the Scopus database. The methodology applied is through a concise searching considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 83 publications
(47 reference statements)
0
27
0
14
Order By: Relevance
“…Criticism of these models led to several further concepts. As Martinez et al (2019) and Kumar et al (2020) showed, two of them are relevant for SME sector.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Criticism of these models led to several further concepts. As Martinez et al (2019) and Kumar et al (2020) showed, two of them are relevant for SME sector.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…Research on the SMEs' capital structure in CEE markets does not have a long tradition and is not as developed as in Western Europe (Mateev et al, 2013;Harc, 2015;Belas et al, 2018;Kenourgios et al, 2019). This assumption is supported by literature review conducted by Martinez et al (2019).…”
Section: Introductionmentioning
confidence: 97%
“…Subsequently, other fields of science adopt it, including studies on corporate finance. Martinez et al (2018) propose the literature's presentation and organization on the capital structure through a systematic review. They use Scopus' database to analyze the small and medium-sized companies' capital structure financial theories.…”
Section: Methodsmentioning
confidence: 99%
“…Структура капитала се у суштини односи на то како предузеће финансира своје укупне активности и напредак коришћењем различитих извора средстава. Другим речима, структура капитала предузећа је резултат низа ситуација, у којима се комбинују одлуке о финансирању предузетника, кредитна ограничења давалаца средстава и тржишни услови, који су сви условљени феноменом асиметричних информација (Martinez, L. B., Scherger, V., & Guercio, M. B., 2019). Структура капитала предузећа може се изразити применом бројних показатеља.…”
Section: структура капитала -преглед литературеunclassified